INFLUENCE OF TERT-BUTYL HYDROPEROXIDE AND NITROSOGLUTATHIONE ON Escherichia coli CELLS EXPRESSING LEGHEMOGLOBIN - Kosmachevskaya O.V.,; Shumaev K.B.; Arredondo-Peter R.; Topunov A.F. (Journal of Stress Physiology & Biochemistry, 2007)
Influence of expressed leghemoglobin on stability of Escherichia coli cells to reactive oxygen and nitrogen species – tert-butyl hydroperoxide and S-nitrosoglutathione was studied. We determined both action of these compounds on cells with different level of leghemoglobin expression and peroxidase activity of the cells. It was shown that priority of pro- or antioxidant properties of leghemoglobin is dependent on its concentration in the cells. In cells with reduced synthesis leghemoglobin mostly functions as prooxidant, in cells with intensive one – as antioxidant.